The activation of digital learning techniques and their role in the development of university education: a case study of the department of Arabic language and literature at the university of 08 may 1945, guelma - messaoudi, fatima; rouabhia, hadda (El Omda in Linguistics and Discourse Analysis, 2025)
education level. We will examine its techniques, analyze its impact, and explore its prospects. Relying on the descriptive method with a focus on the questionnaire, we concluded that despite the existence of some obstacles, digital learning has led to a qualitative leap that enhanced teaching methods, revealed students' talents, and overcame some barriers to scientific researc